2017
DOI: 10.1016/j.jss.2017.06.078
|View full text |Cite
|
Sign up to set email alerts
|

TSG-6 is highly expressed in human abdominal aortic aneurysms

Abstract: Background The formation of abdominal aortic aneurysms (AAA) is characterized by a dominance of pro-inflammatory forces that result in smooth muscle cell apoptosis, extra-cellular matrix degradation, and progressive diameter expansion. Additional defects in the anti-inflammatory response may also play a role, but have yet to be fully characterized. TSG-6 (TNF-stimulated gene-6) is a potent anti-inflammatory protein involved in extracellular matrix stabilization and cell migration active in many pathological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…However, in terms of immunosuppression, the interactive possibility of other immune cells cannot be excluded. IL-10 and TSG-6 are the main anti-inflammatory factors expressed in M2 macrophages [22]. In the present study, iM Φ exhibited the highest increase in the expression levels of IL-10 and TSG-6 as compared to those in other AdMSCs and AdMSCs plus iM Φ .…”
Section: Discussionsupporting
confidence: 49%
“…However, in terms of immunosuppression, the interactive possibility of other immune cells cannot be excluded. IL-10 and TSG-6 are the main anti-inflammatory factors expressed in M2 macrophages [22]. In the present study, iM Φ exhibited the highest increase in the expression levels of IL-10 and TSG-6 as compared to those in other AdMSCs and AdMSCs plus iM Φ .…”
Section: Discussionsupporting
confidence: 49%
“…Recently, new phenotypes of macrophages were described to result from additional stimuli under certain microenvironments. These include hemorrhage-associated macrophages called Mhem (induced by hemoglobin) [ 23 ], macrophages stimulated with oxidized phospholipids (Mox) [ 24 ], and M4 macrophages induced by chemokine ligand 4 [ 25 ], tumor-associated macrophages (TAMs) etc. The currently available data indicate that macrophage polarization is a multifactorial process in which a large number of factors can be involved, producing different activation scenarios (Fig.…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…Recent studies have shown the presence of TSG-6 expression in human coronary atherosclerotic plaques and abdominal aortic aneurysms [ 10 , 48 ]. The expression of TSG-6 is almost absent in normal and non-stenotic coronary arteries from non-CAD and CAD patients respectively [ 10 ].…”
Section: Expression Of Tsg-6 In Human Arteriosclerotic Lesions Anmentioning
confidence: 99%
“…In the stenotic coronary arteries from CAD patients, TSG-6 is highly expressed in the fibrous cap within atherosclerotic plaques [ 10 ]. In addition, the expression of TSG-6 is observed in the tunica media of human abdominal aortic aneurysms [ 48 ]. These findings suggest that TSG-6 is produced to counteract the progression of atherosclerotic lesions and to stabilize vulnerable plaques and aneurysms.…”
Section: Expression Of Tsg-6 In Human Arteriosclerotic Lesions Anmentioning
confidence: 99%